Kick the hive, get the bees: graffiti writers as assemblage and direct action political actors in their battle against H&M. Issue 1 (December 2018) - Mitman, Tyson
Abstract In October of 2017 fast fashion retailers H&M produced an online ad that featured some of Jason 'REVOK' Williams' graffiti in the background. Revok filed a cease and desist order to get H&M to stop using his work in their ad. H&M then sued him, claiming he had no right to copyright protections because the work was produced illegally. This lawsuit became public knowledge and infuriated the global graffiti community, who began a week long worldwide uncoordinated direct action campaign against H&M. Graffiti writers wrote graffiti on H&M storefronts and ideologically attacked H&M in social media spaces until the lawsuit was dropped. This article will examine why graffiti writers responded to the lawsuit against Revok this way, considering these graffiti writers had to undertake great personal risk to commit their acts of vandalism and, because none of them had any personal or financial stake in the outcome of the lawsuit. To understand why graffiti writers acted as they did graffiti as a protest act and as a spectacle will be discussed, as will the importance of subcultural capital. Further this article will explain the motivations of graffiti writers in their fight against H&M and the ways that they use physical and virtual spaces to build their reputations and interact and communicate with each other. Ultimately, this will explain how H&M filing the lawsuit against Revok provided a crucial moment of opportunity that allowed graffiti writers to engage in dramatic public acts of self-promotion. These acts marked writers as politically aware, anti-authoritarians willing to take risks and violate the authoritative aesthetics of the clean and controlled H&M storefronts in support of Revok, which in turn made their acts of graffiti forms of contentious political participation. Through sharing their acts on social media and associating it with the Revok vs. H&M conflict through hashtags, writers further promoted themselves, clearly associated themselves with famous graffiti writer Revok and increased their general presence and their subcultural capital within the graffiti community.